2021
DOI: 10.1128/aac.01208-21
|View full text |Cite
|
Sign up to set email alerts
|

First-in-Human Evaluation of the Safety, Tolerability, and Pharmacokinetics of SPR720, a Novel Oral Bacterial DNA Gyrase (GyrB) Inhibitor for Mycobacterial Infections

Abstract: SPR720 (phosphate pro-drug of SPR719) is a novel aminobenzimidazole bacterial DNA gyrase (GyrB) inhibitor in development for non-tuberculous mycobacterial pulmonary disease (NTM-PD) and pulmonary tuberculosis. SPR719 has demonstrated activity against clinically relevant mycobacteria in vitro and in murine and hollow fiber infection models. This Phase 1 randomized, double-blind, placebo-controlled, single ascending dose (SAD)/multiple ascending dose (MAD) trial evaluated the safety, tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Current therapeutics remain challenging because of the long treatment duration and poor tolerability, with many patients left with residual lung dysfunction (15,17) or failing to respond to treatment, relapsing, or developing macrolide resistance (18). SPR720 is a novel aminobenzimidazole antimicrobial phosphate prodrug that prevents bacterial growth by inhibiting bacterial DNA gyrase (19,20) and is orally bioavailable in humans (21). Specifically, SPR719 targets ATPase located on the bacterial gyrase B subunit of the heterotetrameric gyrase protein, a mechanism that is distinct from fluoroquinolones and other currently marketed antibiotics, so it is unlikely for SPR719 to show cross-resistance with any standard-of-care agents due to alteration of the target enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Current therapeutics remain challenging because of the long treatment duration and poor tolerability, with many patients left with residual lung dysfunction (15,17) or failing to respond to treatment, relapsing, or developing macrolide resistance (18). SPR720 is a novel aminobenzimidazole antimicrobial phosphate prodrug that prevents bacterial growth by inhibiting bacterial DNA gyrase (19,20) and is orally bioavailable in humans (21). Specifically, SPR719 targets ATPase located on the bacterial gyrase B subunit of the heterotetrameric gyrase protein, a mechanism that is distinct from fluoroquinolones and other currently marketed antibiotics, so it is unlikely for SPR719 to show cross-resistance with any standard-of-care agents due to alteration of the target enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized, double-blind, placebo-controlled, phase I clinical trial evaluated the safety, drug resistance, and pharmacokinetics of SPR720. The results showed that SPR720 was well tolerated orally, and the most common adverse events were mild to moderate gastrointestinal reactions and headache, which were shown to be dosedependent (ClinicalTrials.gov Identifier: NCT03796910) [78]. Besides, active compounds with aromatic skeleton structures were identified through high-throughput screening, and they showed desirable gyrB inhibitory and anti-Mtb activities in vitro (Figure 2(c)) [79][80][81] and then religating the seal.…”
Section: Dna-related Enzymesmentioning
confidence: 99%
“…Recently, a novel benzimidazole (SPR719, Fig. 1A ) entered early clinical development for mycobacterial lung diseases ( 19 ). Benzimidazoles target the ATPase domain of the DNA gyrase complex, located on its B subunits and required to drive the catalytic cycle ( 20 ), distinct from the fluoroquinolone binding site.…”
Section: Textmentioning
confidence: 99%